Avaliação da espessura das tábuas ósseas alveolar vestibular e lingual dos maxilares, por meio da tomografia computadorizada de feixe cônico (cone beam) - Ferreira, Marcos Cezar (2010)
This prospective study aimed at evaluating, by means of cone-beam computed tomography (CBCT), the buccal and lingual bone plate thickness of maxillary and mandibular permanent teeth. The sample comprised 30 CBCT exams of patients of both sexes, with age ranging from 10,1 to 37,2 years, acquired with i-Cat (Xoran Technologies, Ann Arbor, Mich/ Imaging Sciences International, Hatfield, Pa) and analized using Nemoscan and Nemoceph softwares. A quantitative evaluation was performed by a calibrated examiner using the palatal plane as reference for the maxillary axial sections and the corrected occlusal plane for the mandibular axial sections. Means and standard deviations of buccal and lingual bone plate thickness was obtained for each permanent teeth. The bone thickness was compared in patients with different facial patterns, ages and sexes using independent t tests. The intra-examiner systematic and casual error was verified using dependent t test and Dalhberg formula, respectively. The data was considered using a 5% significance level. The buccal bone plate was thinner than the lingual bone plate in the maxilla and mandible. The maxilla showed a thicker buccal bone plate than the mandible in the cervical region. The lingual bone plate thickness of anterior teeth was greater in the maxilla than in the mandible. In the majority of permanent teeth, the buccal and lingual bone plate thickness was not different in the growth pattern subgroups. No sexual difference and slight age differences were observed for the buccal and lingual bone plate thickness.